A myco-ecological analysis (lignicolous Aphyllophorales sensu lato, Basidiomycota) of the Abies pinsapo, Quercus and Pinus forests of Andalusia (southern Spain) (Nova Hedwigia, 2004)
This paper presents a mycological inventory (lignicolous Aphyllophorales) of five substrates that are characteristic of Mediterranean vegetation in Andalusia: Abies pinsapo, Quercus faginea, Quercus ilex subsp. ballota, Quercus suber and Pinus sp. pl. The species richness of each substrate was determined and related to the number of vegetation series to which these tree species belong. A series of parameters were used to determine the myco-ecological relationships in the substrates, namely the level of affinity proposed by Goslee, the level of similarity (Sørensen’s quantitative index) and the level of diversity (degree of alpha diversity). A correspondence analysis was also carried out.